Gastrin, Histamine Prostaglandin: Indicators for assessing efficacy of cimetidine, Omeprazole and Ranitidine in Gastric Ulcer Treatment - Okon, Jimmy Etukudo; Egesie, Gideon Umezuruike (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: There is increase prevalence of gastric ulcer in the society, but the drugs that are sensitive for radical cure are not screened with physiologic markers such which affect proper management of the disease. The objective of the study is to relate various sources or organ specific templates: gastrin, histamine and prostaglandin relating with the disease in evaluating the potencies of cimetidine, ranitidine and omeprazole for best choice of the drugs in gastric ulcer disease treatment. Material and Methods: Plasma, gastric and antral prostaglandins, histamine and gastrin levels were studied in ninety-six (96), male and female Swiss albino rats for 28 days, using high performance liquid chromatography. Results: Male and female rats with gastric ulcer treated with cimetidine, omepraszole and ranitidine showed no significant difference (P>0.5) in gastrin and the drug groups in plasma, gastric and antral concentrations. But, there was significant difference (P<0.05) in histamine levels between cimetidine, omeprazole and ranitidine in their gastric and plasma concentration. There was no significant difference (P>0.05) in prostaglandin values between cimetidine, omeprazole and ranitidine. Also there was no significant difference (P>0.05) in gastric and plasma levels of gastrin, histamine and prostaglandin between 7, 14, 21 and 28 days treatment period. But, there was significant difference (P<0.05) in antral concentration of gastrin, histamines and prostaglandin between the drug groups. However, there was no significant difference (P>0.05) in antral gastrin between male and female rats in cimetidine and ranitidine treatment. The three drugs were associated with high levels of gastrin, histamine, low prostaglandin though cimetidine showed higher concentration of prostaglandin. Conclusion: It is concluded that gastrin, histamine and prostaglandin are sensitive indicators in evaluating anti-ulcerogenic drugs efficacies. Janaki Medical College Journal of Medical Sciences (2017) Vol. 5(2): 5-12